APPLICATION OF THE AUDIO-VISUAL-BASED PAIRED-STORYTELLING METHOD: ENHANCING STUDENTS' SPEAKING SKILLS - Ayu Made Wedasuwari, Ida; Ni Wayan Eminda Sari (International Journal of Social Science, 2025)
This study addresses a significant research gap by integrating paired storytelling with audiovisual tools to enhance students' speaking skills through active participation, emotional engagement, and technological support, moving beyond traditional content-focused approaches. It explores the implementation and effectiveness of paired storytelling in improving the speaking skills of fifth-semester students in the Indonesian Language and Literature Education Program at FKIP Universitas Mahasaraswati Denpasar. The study contributes to developing innovative teaching strategies that foster communication skills and critical thinking by answering whether and how the paired storytelling method enhances speaking performance. A classroom action research design comprised three stages: pre-cycle, Cycle 1, and Cycle 2. Data were collected through tests and direct practice sessions. Baseline performance was established in the pre-cycle phase, while subsequent cycles implemented and refined the paired-storytelling method to assess its impact. The findings revealed significant improvements in students' speaking skills. In the pre-cycle, the average score was 64.2, with most students scoring below the success indicator 80. After implementing the method in Cycle 1, the average score rose to 79.0, with 80% meeting the criteria. By Cycle 2, all students surpassed the indicator, achieving an average score of 89.73. These results underscore the method's effectiveness in fostering confidence and improving linguistic abilities